Qardhul Hasan dalam Persfektif Hukum Islam pada Baitul Maal wa Tamwil (BMT) dan Implementasinya - Muhamad Bisri Mustofa; Mifta Khatul Khoir (Institut Agama Islam Agus Salim Metro Lampung, 2020)
Abstract In the implementation of Islamic Financial Institutions such as the Baitul Maal wa Tamwil (BMT) there are various ways of collecting funds and channeling funds. Funds are collected through wadi'ah deposits and deposits. While the distribution of funds is done by murabahah, mudharabah, musyarakah, rahn (pawn), ijarah, ijarah multijasa and qardhul hasan financing. Qardhul Hasan's financing is the orientation of the function of the Islamic Financial Institution (Baitul Maal Wa Tamwil) as a social institution. Qardhul hasan is a soft loan given on the basis of mere social obligations. In this case the borrower is not required to return anything except the amount borrowed. In Qardhul Hasan financing there are pillars and conditions, namely the perpetrator of the contract consisting of muqtaridh (borrower), muqridh (lender), qardh (fund), shighat ijab and qabul willingness for both parties and funds used for something useful and lawful. Qardhul Hasan is an activity to achieve a predetermined goal or target by the relevant Islamic financial institutions. The mechanism for implementing Qardhul Hasan is solely aimed at providing assistance to meet the needs of small communities. Thus it can be seen that the form of borrowing through Qardhul Hasan is in accordance with the principles of sharia economic law, the potential source of Qardhul Hasan's funding is quite large if it is utilized and managed optimally and its implementation is very useful for the community. Keywords: Qardhul Hasan, Islamic Law, BMT